Exploring the "Athlete's Paradox": Division I Cross-Country Runners Demonstrate Similar Muscle Characteristics to Recreationally Trained Young Adults. Issue 11 (November 2021) - Cabre, Hannah E.; Greenwalt, Casey E.; Gould, Lacey M.; Hirsch, Katie R.; Blue, Malia N.M.; Smith-Ryan, Abbie E.
Abstract : Abstract: Cabre, HE, Greenwalt, CE, Gould, LM, Hirsch, KR, Blue, MNM, and Smith-Ryan, AE. Exploring the "Athlete's Paradox": Division I cross-country runners demonstrate similar muscle characteristics to recreationally trained young adults. J Strength Cond Res 35(11): 3213–3217, 2021—Endurance training can influence body composition and muscle characteristics. Endurance athletes have demonstrated elevated intramuscular fat (IMF), yet individuals with greater body fat also demonstrate elevated IMF. The purpose of this study was to examine differences in muscle characteristics (echo intensity [EI] and muscle cross-sectional area [mCSA]) and body composition between Division I collegiate athletes and college-age adults matched for percent fat (%fat). Thirty cross-country athletes (XC) and 30 normal-weight (NW) recreationally active college students (male athletes: n = 30; female athletes: n = 30; mean ± SD : age: 19.2 ± 1.1 years; body mass: 61.7 ± 8.7 kg; %fat: 18.0 ± 5.2%) underwent a panoramic ultrasound scan of the vastus lateralis to evaluate EI and mCSA. A full-body dual-energy x-ray absorptiometry scan was used to assess fat mass (FM), lean mass (LM), and %fat. Independent t -tests were used to evaluate mCSA, EI, and body composition. Significance level was set at ⩽ 0.05. There were no significant differences between the XC and NW cohorts in mCSA (mean difference [MD; XC − NW], −1.30 ± −0.40 cm 3 ; p = 0.340) or EI (MD: 3.97 ± 2.66 a.u.; p = 0.478). Body composition was not different between the groups: FM (MD: −0.14 ± −0.54 kg; p = 0.848), LM (−3.07 ± 1.25 kg; p = 0.268), or bone mineral content (−0.21 ± 0.03 kg; p = 0.120). There were also no significant differences for any outcome variables when stratified by male athletes ( p = 0.097–0.468) or female athletes ( p = 0.055–0.700). These results suggest that XC athletes may have similar muscle characteristics to NW individuals when matched for %fat. Understanding and tracking muscle characteristics in XC athletes may be important for performance, injury prevention, and the transition to retirement.